1984
DOI: 10.2514/3.19896
|View full text |Cite
|
Sign up to set email alerts
|

Minimal root sensitivity in linear systems

Abstract: Nominal performance, root sensitivity, and stability are important control design considerations. This paper deals only with the first two of these concerns. A lower bound is derived for root sensitivity and necessary and sufficient conditions are given to achieve this minimum. This is the main result of the paper. In addition, an optimal output feedback control problem is discussed which penalizes an index related to root sensitivity. Two hazards are clarified concerning root sensitivity designs. First, we il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is easy to see that (26) and so (25) leads to the following transfer function sensitivity measure:…”
Section: B Transfer Function Sensitivity Measurementioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to see that (26) and so (25) leads to the following transfer function sensitivity measure:…”
Section: B Transfer Function Sensitivity Measurementioning
confidence: 99%
“…Mantey [25] showed that the poles/eigenvalues are dependent on the state-space realization. It is wellknown that an eigenvalue sensitivity is minimized if the system is normal [26]. However Gevers and Li [5] subsequently determined the realization that would minimize a pole sensitivity measure combined with a zero sensitivity measure proposed in [27].…”
Section: Introductionmentioning
confidence: 98%